HUBUNGAN PENGETAHUAN PETERNAK DENGAN KETERAMPILAN PEMBERIAN PAKAN LOKAL PADA TERNAK SAPI POTONG DI KECAMATAN BAWANG KABUPATEN BANJARNEGARA - Sakti, Dian Putri Maulia; Setianto, Novie Andri; Yuwono, Pambudi (ANGON: Journal of Animal Science and Technology, 2021)
Backgrund. This study aims to determine breeders 'knowledge and local feeding skills for beef cattle and to analyze the relationship between breeders' knowledge and local feeding skills for beef cattle in Bawang District, Banjarnegara Regency. The characteristics of breeders 'skills studied were farmer education level, age of breeders, and length of breeding in feeding balance, composition of feed and frequency of local feeding as well as breeders' knowledge of local feed. Materials and Methods. The research method used is a survey method. The determination of the sample area was carried out by purposive sampling method, namely taking areas that have a group of beef cattle breeders in Bawang District. Respondents were collected using the census method, namely by selecting members of the livestock farmer groups who were active and kept livestock in the last one year. The total number of respondents was 40 people, and the test used was the descriptive test and the Spearman rank correlation test. Results. The results showed that the level of knowledge of breeders in Bawang District was in the medium category. Skills in moderate feed composition, not skilled in determining the balance of feed and very skilled in frequency of feeding. The results of the spearman rank correlation analysis between breeders' knowledge and local feeding skills have a significant relationship with a strong correlation value of 0,411. This illustrates that with sufficient knowledge, the skills of farmers are sufficiently supportive in providing local feed to livestock. Knowledge has a positive influence on breeders' skills, so that increased knowledge about local feed will also be followed by increasing farmer skills in local feeding. Conclusion. The conclusion of the study is that there is a correlation between breeders' knowledge and local feeding skills in the highly skilled category of feeding frequency.